Physicochemical properties of crude elateriospermum tapas seeds oil - Jumat Salimon; Ooi , Yong Yong (Universiti Kebangsaan Malaysia, 2005)
The crude oil of perah, Elateriospermum tapos, seeds collected from northern Perak was extracted. The chemical properties of extracted oil such as acid value, free fatty acids percentage, iodine value, peroxide value and saponification value were analyzed. The oil physical characteristics such as viscosity, refractive index and color were also determined. The fatty acids composition of the extracted oil was determined using the gas chromatography (GC) method. Both oleic acid (34.55 %) and linoleic acid (31. 76 %) were detected as the dominant fatty acids while palmitic acid and stearic acid were the saturated fatty acids found in the perah seeds oil. Unlike most seed oils, perah seeds oil contained α-linoleneic acid (16.10%) as part of its five major fatty acids composition. Results from analyses showed that perah seeds oil is a potential nutritive seeds oil to be developed in the future.